ANALYSIS OF THE WJP RULE OF LAW INDEX DATA, EXAMINATION OF ITS ASSESSMENT METHODOLOGY, AND EVALUATION OF PROBLEMS AND SHORTCOMINGS IDENTIFIED IN THE KEY AREAS REFLECTED IN THE INDEX - Jurakulov Biloliddin Srojiddinovich (Sciental Journals Publishing, 2025)
This article provides a comprehensive analysis of the data of the Rule of Law Index developed by the World Justice Project (WJP) and offers an in-depth examination of the criteria and methodological principles applied in its formation. Within the framework of the study, the main structural dimensions of the Index are analyzed in detail, including constraints on government powers, absence of corruption, open government, protection of fundamental rights, order and security, effectiveness of regulatory enforcement, as well as the independence of civil and criminal justice systems.In addition, the problems and shortcomings identified in various countries through the WJP Index are examined from a comparative legal perspective, and the factors negatively affecting the enforcement of the rule of law are identified. The study substantiates the interconnection between the Index results and the quality of public administration, the effectiveness of the judicial system, the actual level of protection of human rights, and the mechanisms for combating corruption. The findings of this research are expected to serve as an important scientific and practical basis for assessing and improving national reforms aimed at strengthening the rule of law.
Keywords: Rule of Law Index, World Justice Project (WJP), rule of law, indexing criteria, corruption, open government, judicial system, human rights, legal state, regulatory enforcement.